Effects of transcranial direct current stimulation combined with Bosu ball training on the injury potential during drop landing in people with chronic ankle instability - Huang, Xueke; Gao, He; Fu, Haitao (Frontiers in Physiology, 2024)
Purpose: To investigate the effects of transcranial direct current stimulation (tDCS) combined with Bosu ball training on the injury potential during drop landing in people with chronic ankle instability (CAI). Methods: A total of 40 participants with CAI were recruited and randomly divided into the tDCS+Bosu and Bosu groups. The people in the tDCS+Bosu group received intervention of tDCS combined with Bosu ball training, and those in the Bosu group received intervention of sham tDCS and Bosu ball training, for 6 weeks with three 20-minute sessions per week. Before (week0) and after (week7) the intervention, all participants drop-landed on a trap-door device, with their affected limbs on a moveable platform, which could be flipped 24° inward and 15° forward to mimic an ankle inversion condition. The kinematic data were captured using a twelve-camera motion capture system. Two-way ANOVA with repeated measures was used to analyze data. Results: Significant group-byintervention interactions were detected in the peak ankle inversion angular velocity (p=0.047, η 2 p=0.118), the time to peak ankle inversion (p=0.030, η 2 p=0.139), and the plantarflexion angle at the moment of peak ankle inversion (p=0.014, η 2 p=0.173). Post hoc comparisons showed that compared with week0, the peak ankle inversion angular velocity and the plantarflexion angle at the moment of peak ankle inversion were reduced, the time to peak ankle inversion was advanced in both groups at week7, and the changes were greater in the tDCS+Bosu group compared to the Bosu group. And, a significant intervention main effect was detected in the peak ankle inversion angle in the two groups (p<0.001, η 2 p=0.337). Conclusion: Compared with the Bosu ball training, the tDCS combined with Bosu ball training was more effective in reducing the injury potential during drop landing in people with CAI.